EFFECT OF DIETARY FIBRES ON MICROBIOTA LARGE INTESTINE OF SICK AT ALLOXAN DIABETES RATS - I. В. Страшнова; З. Є. Захарієва; Ю. Ю. Дуденко; А. О. Данилова; В. О. Iваниця (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2010)
It was shown that the taxonomic composition of the large intestine of healthy rats and rats with alloxan diabetes was presented by microorganisms genera Lactobacillus, Escherichia, Enterococcus, Enterobacter, Staphylococcus, Proteus, Bacillus and Candida. The number of bacteria genera Lactobacillus and Escherichia in the intestine of healthy rats was higher than animals with alloxan diabetes in the intestine which in large quantities identified bacteria of genera Staphylococcus, Proteus, Bacillus, Candida. Use of dietary fibers from sugar beet had a positive impact on increasing the number of bacteria genera Lactobacillus and Escherichia both healthy rats and rats with alloxan diabetes.